Electrolyte and lithium battery using same

By adding functional additives containing hydroxyflavonoids to the lithium battery electrolyte, a dense CEI film is formed, which solves the problems of circulation capacity and voltage attenuation of high-voltage lithium batteries, and improves the battery's cycle stability and lithium ion transmission efficiency.

CN119297399APending Publication Date: 2025-01-10EVE ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411310775.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the charging and discharging cycle of high-voltage lithium batteries, the increase in the electrode potential of the positive electrode material leads to the oxidation and decomposition of the interface between the electrolyte and the positive electrode and increase the side reaction, resulting in an increase in the internal resistance of the battery, which in turn affects the cycle stability and energy density of the battery.

Method used

Specific functional additives, such as flavonoids containing hydroxyl groups in the structure, form a dense and uniform electrolyte membrane (CEI membrane) to protect the positive electrode interface, inhibit the dissolution of transition metal ions and the release of oxygen, and promote the rapid transmission of lithium ions.

Benefits of technology

By forming a stable CEI film, the cycle stability and lithium ion utilization efficiency of the lithium battery are improved, and the circulation capacity and voltage retention ability of the battery are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297399A_ABST
    Figure CN119297399A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a lithium battery using the same, the electrolyte comprises an electrolyte additive, the electrolyte additive comprises a functional additive, and the structure of the functional additive is as shown in formula I; # imgabs0 # R1, R2, R3, R4, R5, R6, R7, R8, R9 and R10 are respectively and independently selected from one of hydrogen, C1-10 straight chain or branched chain alkyl or alkoxy and C1-10 halogenated straight chain or branched chain alkyl or alkoxy, and at least one of R1, R2, R3, R4, R5, R6, R7, R8, R9 and R10 is hydroxyl. By adopting the specific functional additive as the electrolyte additive, a stable CEI film can be formed on the surface of the positive electrode, and the chemical composition of the CEI film is regulated in situ, so that the problems of relatively fast cycle capacity attenuation and relatively fast voltage attenuation of a high-voltage material system battery are solved, and the battery has excellent cycle characteristics and lithium ion utilization efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to an electrolyte and a lithium battery using the electrolyte. Background Art

[0002] The continued prosperity of computers, communications and consumer electronics has brought about the rapid development of the lithium battery industry. In particular, the rise of new energy vehicles in recent years has not only promoted the development of power lithium batteries, but also put forward higher energy density and safety performance. The endurance of electric vehicles has become one of the performance indicators that consumers are most concerned about, and the energy density of the battery determines the single mileage of electric vehicles. How to improve the energy density of the battery under limited space and weight has become a hot topic of research by all parties. Increasing the working voltage of the positive electrode material is a major way to improve the energy density of lithium batteries. At present, high-voltage positive electrode materials, such as lithium nickel manganese oxide (LNMO), high-voltage ternary, high-voltage lithium cobalt oxide, layered lithium-rich oxide (LLO), etc. have become research hotspots. As the voltage of lithium batteries continues to increase, the positive electrode material will have a higher electrode potential, the oxidation decomposition of the electrolyte at the positive electrode and the positive electrode interface reaction will be more intense, and as the battery charge and discharge cycle continues, the internal resistance of the battery gradually increases, which in turn causes the battery performance to decline or even fail.

[0003] At present, researchers mainly overcome these defects by modifying the cathode material or adjusting the electrolyte formula. However, the cathode material modification method is complex and costly, while adjusting the electrolyte components is simple to operate, has obvious effects, and is conducive to industrial application. Therefore, how to adjust the electrolyte formula to improve the interface stability between the electrolyte and the cathode is a technical problem that technicians in this field need to solve urgently in their research. Summary of the invention

[0004] The purpose of the present invention is to provide an electrolyte additive, wherein the functional additive in the electrolyte can form a stable CEI film on the positive electrode surface and in situ regulate the chemical composition of the CEI film, thereby effectively protecting the positive electrode interface and making the lithium battery using the additive have excellent cycle stability and lithium ion utilization efficiency.

[0005] According to one aspect of the present invention, an electrolyte is provided, the electrolyte includes an electrolyte additive, the electrolyte additive includes a functional additive, and the structure of the functional additive is shown in Formula I;

[0006]

[0007] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R7 , R 8 , R 9 , R 10 are independently selected from hydrogen, C1-10 straight or branched alkyl or alkoxy, C1-10 halogenated straight or branched alkyl or alkoxy, and R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 At least one of them is a hydroxyl group.

[0008] The present invention introduces a functional additive having a structure as shown in Formula I into the electrolyte. The hydroxyl contained in the flavonoid structure of the functional additive is easily oxidized, so that a dense and uniform CEI film is formed on the positive electrode surface. The CEI film can inhibit the dissolution of transition metal ions and the release of oxygen, reduce the side reaction between the electrolyte and the positive electrode interface, improve the stability of the interface, and effectively protect the positive electrode interface. The CEI film can promote the rapid transmission of lithium ions in the electrolyte and the positive electrode surface, so that the lithium ion transmission dynamic characteristics and cycle stability of the battery are improved. In summary, the present invention adopts a specific functional additive as an electrolyte additive to form a stable CEI film on the positive electrode surface, and in situ regulates the chemical composition of the CEI film, thereby solving the problem of rapid cycle capacity decay and voltage decay of high-voltage material system batteries, so that the battery has excellent cycle characteristics and lithium ion utilization efficiency.

[0009] Preferably, in Formula I, R 1 , R 2 , R 3 , R 4 , R 5 At least two of them are hydroxyl groups, and R 7 , R 8 , R 9 , R 10 At least two of them are hydroxyl groups. The hydroxyl groups contained in the flavonoid structure of the functional additive are more easily oxidized, so that a dense and uniform CEI film is formed on the surface of the positive electrode, thereby fully protecting the positive electrode and further improving the cycle stability of the lithium battery using the additive.

[0010] Preferably, the mass proportion of the functional additive in the electrolyte is 0.3% to 1.0%. By controlling the content of the functional additive in the electrolyte, it is beneficial for the functional additive to form a dense and uniform CEI film on the positive electrode surface, preventing the problem of excessive film formation causing the battery impedance to increase and the cycle performance to decrease, thereby further improving the cycle stability of the battery.

[0011] Preferably, the electrolyte additives also include sulfur-containing additives, carbonate additives and lithium salt additives. The introduction of the above additives is conducive to promoting the formation of a good CEI film on the positive electrode surface, thereby improving the structural stability and cycle stability of the battery.

[0012] Preferably, the sulfur-containing additive includes at least one of methylene disulfonate (MMDS) and vinyl sulfate (DTD); the carbonate additive includes vinyl carbonate (VC); the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), and lithium tetrafluoroborate (LiBF4). The combination of the above-mentioned specific sulfur-containing additive and lithium salt additive can assist the above-mentioned functional additive to form a good CEI film on the positive electrode surface and ensure the compactness and stability of the generated CEI film; at the same time, the above-mentioned specific sulfur-containing additive, lithium salt additive and carbonate additive can work together to promote the formation of a good SEI film on the negative electrode surface. Therefore, the above-mentioned specific carbonate additive, lithium salt additive, sulfur-containing additive and functional additive can play a synergistic role and improve the interface stability between the electrolyte and the positive and negative electrodes; in addition, it can also improve the stability and density of the CEI film, effectively inhibit the dissolution of positive electrode metal ions, and reduce the damage of metal ions to the CEI film, so that the cycle stability of the battery and the effective utilization rate of lithium ions are further improved.

[0013] Preferably, the mass proportion of sulfur-containing additives in the electrolyte is 0.5% to 1.0%; the mass proportion of carbonate additives in the electrolyte is not higher than 0.5%; the mass proportion of lithium salt additives in the electrolyte is 0.3% to 1.0%; the mass proportion of functional additives in the electrolyte is 0.3% to 1.0%. By controlling the content of carbonate additives, lithium salt additives, sulfur-containing additives, and functional additives within a reasonable range, it is beneficial for the components of the electrolyte additives to fully exert their synergistic effects, promote the formation of dense and uniform CEI films and SEI films on the positive and negative electrode surfaces, thereby improving the interface stability between the electrolyte and the positive and negative electrode surfaces, and improving the cycle stability of the battery system.

[0014] Preferably, the mass proportion of the electrolyte additive in the electrolyte does not exceed 5%.

[0015] Preferably, the electrolyte further comprises an organic solvent, and the organic solvent comprises cyclic carbonate, chain carbonate and chain carboxylic acid ester.

[0016] Preferably, calculated by mass ratio, cyclic carbonate: chain carbonate: chain carboxylate = 1-20: 15-70: 5-20. Cyclic carbonate, chain carbonate, and chain carboxylate are compounded in a specific ratio in an organic solvent. On the one hand, the decomposition of the electrolyte in a high temperature environment can be inhibited, and the occurrence of side reactions between the electrode material and the electrolyte can be reduced. At the same time, the rapid transmission of lithium ions in the electrolyte in a low temperature environment can be promoted, so that the electrolyte can be used in a working environment with a wide temperature range, giving the lithium battery good high and low temperature charge and discharge performance; on the other hand, the above-mentioned organic solvent has the advantages of high dielectric constant and low viscosity, which can promote the dissolution and dispersion of lithium salts and electrolyte additives, so that each component of the electrolyte can fully play its respective advantages, ensuring the compactness and uniformity of the CEI film formed on the surface of the positive electrode, thereby further improving the electrochemical performance of the battery.

[0017] Preferably, the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.

[0018] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0019] Preferably, the chain carboxylic acid ester includes at least one of methyl formate, methyl acetate, and ethyl difluoroacetate.

[0020] Preferably, the electrolyte further includes lithium salt, and the mass proportion of the lithium salt in the electrolyte is 10% to 15%.

[0021] Preferably, the mass proportion of the organic solvent in the electrolyte is 80% to 88%.

[0022] According to another aspect of the present invention, a lithium battery is provided, comprising the above-mentioned electrolyte. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0024] Example 1

[0025] Treatment Group 1-1

[0026] The processing group provides an electrolyte solution, which consists of an organic solvent, a lithium salt and an electrolyte additive.

[0027] Electrolyte additives include sulfur-containing additives, carbonate additives, lithium salt additives and functional additives. The mass proportion of electrolyte additives in the electrolyte is 1.4%.

[0028] Carbonate additives include vinylene carbonate (VC), and the mass proportion of VC in the electrolyte is 0.2%;

[0029] Sulfur-containing additives include lithium bis(fluorosulfonyl)imide (LiFSI), with LiFSI accounting for 0.4% by mass in the electrolyte;

[0030] The lithium salt additive includes methylene disulfonate (MMDS), and the mass proportion of the lithium salt additive in the electrolyte is 0.5%;

[0031] The functional additive includes 3'-hydroxyflavanone, the structure of which is shown in Formula II;

[0032] The mass percentage of functional additives in the electrolyte is 0.3%;

[0033] The lithium salt is lithium hexafluorophosphate, and the mass percentage of lithium hexafluorophosphate in the electrolyte is 14%;

[0034] The content of organic solvent in the electrolyte accounts for 84.6%. Taking the total mass of organic solvent as 100%, the organic solvent is composed of 15wt% cyclic carbonate (ethylene carbonate), 70wt% chain carbonate (dimethyl carbonate), and 15wt% chain carboxylic acid ester (ethyl difluoroacetate).

[0035] The electrolyte provided by the treatment group is prepared by the following steps: under an argon atmosphere, an electrolyte additive is added to an organic solvent, and then a lithium salt is added, and the mixture is stirred and mixed at 10° C. to prepare an electrolyte.

[0036] Treatment Group 1-2

[0037] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula III;

[0038]

[0039] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0040] Treatment Groups 1-3

[0041] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula IV;

[0042]

[0043] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0044] Treatment Groups 1-4

[0045] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula V;

[0046]

[0047] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0048] Treatment Groups 1-5

[0049] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula VI;

[0050]

[0051] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0052] Treatment Groups 1-6

[0053] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula VII;

[0054]

[0055] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0056] Treatment Groups 1-7

[0057] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula VIII;

[0058]

[0059] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0060] Treatment Groups 1-8

[0061] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula IX;

[0062]

[0063] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0064] Treatment Groups 1-9

[0065] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the mass proportion of the functional additive in the electrolyte in this treatment group is 0.2%. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0066] Treatment Groups 1-10

[0067] This treatment group prepared the electrolyte with reference to treatment group 1-1. The difference between this treatment group and treatment group 1-1 is that the mass proportion of the functional additive in the electrolyte in this treatment group is 1.2%. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.

[0068] Comparative treatment group 1-1

[0069] The electrolyte of this comparative treatment group is prepared with reference to treatment group 1-1. The difference between this comparative treatment group and treatment group 1-1 is that the electrolyte additives used in this comparative treatment group do not contain functional additives. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 1-1.

[0070] Comparative treatment group 1-2

[0071] The electrolyte of this comparative treatment group is prepared by referring to treatment group 1-1. The difference between this comparative treatment group and treatment group 1-1 is that the structure of the functional additive in this comparative treatment group is shown in formula Ⅺ;

[0072]

[0073] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 1-1.

[0074] Comparative treatment groups 1-3

[0075] The electrolyte of this comparative treatment group is prepared by referring to treatment group 1-1. The difference between this comparative treatment group and treatment group 1-1 is that the structure of the functional additive in this comparative treatment group is shown in formula XII;

[0076]

[0077] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 1-1.

[0078] Example 2

[0079] Treatment Group 2-1

[0080] This treatment group prepared the electrolyte according to treatment group 1-1, and the materials and process operations used in this treatment group were strictly consistent with those of treatment group 1-1.

[0081] Treatment group 2-2

[0082] This treatment group prepared the electrolyte with reference to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of vinyl sulfate (DTD) was used in this treatment group to replace the MMDS in treatment group 2-1 as the sulfur-containing additive. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 2-1.

[0083] Treatment Group 2-3

[0084] The electrolyte of this treatment group was prepared by referring to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of lithium bis(oxalatoborate) (LiBOB) was used as a lithium salt additive instead of LiFSI in treatment group 2-1. In addition to the above differences, the materials and process operations used in this treatment group were strictly consistent with those of treatment group 2-1.

[0085] Treatment Groups 2-4

[0086] This treatment group prepared the electrolyte with reference to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of 1,3-propane sultone (PS) was used in this treatment group to replace the MMDS in treatment group 2-1 as the sulfur-containing additive. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 2-1.

[0087] Treatment Groups 2-5

[0088] The electrolyte of this treatment group was prepared by referring to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the electrolyte of this treatment group was prepared by using the same mass of lithium difluorophosphate (LiPO 2 F 2) replaces LiFSI in treatment group 2-1 as the lithium salt additive. Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 2-1.

[0089] Comparative treatment group 2-1

[0090] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-1. The difference between this comparative treatment group and treatment group 2-1 is that the structure of the functional additive in this comparative treatment group is shown in formula X;

[0091]

[0092] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-1.

[0093] Comparative treatment group 2-2

[0094] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-2. The difference between this comparative treatment group and treatment group 2-2 is that the structure of the functional additive in this comparative treatment group is shown in formula X;

[0095]

[0096] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-2.

[0097] Comparative treatment group 2-3

[0098] The electrolyte of this comparative treatment group is prepared by referring to treatment group 2-3. The difference between this comparative treatment group and treatment group 2-3 is that the structure of the functional additive in this comparative treatment group is shown in formula X;

[0099]

[0100] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-3.

[0101] Comparative treatment groups 2-4

[0102] The electrolyte of this comparative treatment group is prepared by referring to treatment group 2-4. The difference between this comparative treatment group and treatment group 2-4 is that the structure of the functional additive in this comparative treatment group is shown in formula X;

[0103]

[0104] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment groups 2-4.

[0105] Comparative treatment groups 2-5

[0106] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-5. The difference between this comparative treatment group and treatment group 2-5 is that the structure of the functional additive in this comparative treatment group is shown in formula X;

[0107]

[0108] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment groups 2-5.

[0109] Comparative treatment groups 2-6

[0110] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-1. The difference between this comparative treatment group and treatment group 2-1 is that the functional additive in treatment group 2-1 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC). In addition to the above differences, the materials and process operations used in this comparative treatment group were strictly consistent with those of treatment group 2-1.

[0111] Comparative treatment groups 2-7

[0112] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-2. The difference between this comparative treatment group and treatment group 2-2 is that the functional additive in treatment group 2-2 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC) in this comparative treatment group. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-2.

[0113] Comparative treatment groups 2-8

[0114] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-3. The difference between this comparative treatment group and treatment group 2-3 is that the functional additive in treatment group 2-3 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC) in this comparative treatment group. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-3.

[0115] Comparative treatment groups 2-9

[0116] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-4. The difference between this comparative treatment group and treatment group 2-4 is that the functional additive in treatment group 2-4 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC). In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-4.

[0117] Comparative treatment group 2-10

[0118] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-5. The difference between this comparative treatment group and treatment group 2-5 is that the functional additive in treatment group 2-5 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC) in this comparative treatment group. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-5.

[0119] Test Example 1

[0120] 1. Test object:

[0121] The electrolyte prepared in Examples 1 to 2 was used to prepare a lithium battery. The preparation method of the lithium battery was as follows: a negative electrode material graphite, a conductive agent acetylene black, and a binder CMC and SBR were prepared in a mass percentage of 94:1:2:3 to form a negative electrode slurry, which was coated on a copper foil current collector and vacuum dried to obtain a negative electrode sheet; a positive electrode material 0.25Li 2 MnO 3 0.75LiMn 0.375 Ni 0.375 Co 0.25 O 2 , acetylene black as a conductive agent and PVDF as a binder are prepared into a positive electrode slurry in a mass ratio of 94:3:3 and coated on an aluminum foil current collector, and vacuum dried to obtain a positive electrode sheet. The positive electrode sheet, the negative electrode sheet, Celgard2400 separator and the electrolyte are assembled into a soft pack battery. The obtained battery is used as the test object of this test example.

[0122] 2. Test items:

[0123] (1) Normal temperature cycle performance test:

[0124] At 25°C, the lithium-ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times at 25°C under the above conditions.

[0125] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0126] The average voltage (V) of a lithium-ion battery after N cycles = discharge energy of the Nth cycle / discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.

[0127] (2) High temperature cycle performance test:

[0128] At 45°C, the lithium-ion battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is subjected to 800 charge and discharge cycles at 45°C under the above conditions.

[0129] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0130] The average voltage (V) of a lithium-ion battery after N cycles = discharge energy of the Nth cycle / discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.

[0131] 3. Test results:

[0132] Table 1. Performance test results of Example 1

[0133]

[0134]

[0135] The test results are shown in Table 1. The performance test results of treatment group 1-1 were compared with those of comparison treatment groups 1-1 to 1-3. As shown in Table 1, under the same conditions of other materials and operations for preparing the battery, the electrolyte additives used in comparison treatment group 1-1 do not include functional additives, and the functional additives used in comparison treatment groups 1-2 and 1-3 do not contain flavonoid structures, and the cycle capacity retention rate and average voltage of the batteries prepared in this way at 25°C and 45°C are lower than those of treatment group 1-1. This shows that, compared with the control treatment groups 1-1 to 1-3, the treatment group 1-1 introduces a functional additive with a structure as shown in Formula I into the electrolyte. The hydroxyl group contained in the flavonoid structure of the functional additive is easily oxidized, so that a dense and uniform CEI film is formed on the positive electrode surface. The CEI film can inhibit the dissolution of transition metal ions and the release of oxygen, reduce the side reactions between the electrolyte and the positive electrode interface, improve the stability of the interface, and effectively protect the positive electrode interface. The CEI film can promote the rapid transmission of lithium ions in the electrolyte and the positive electrode surface, thereby improving the normal high temperature cycle performance and lithium ion utilization efficiency of the battery.

[0136] By comparing the performance test results of treatment groups 1-1 to 1-8 in Example 1 with those of treatment groups 1-9 to 1-10, it can be found that the cycle capacity retention rate and average voltage at 25°C and 45°C of the batteries prepared from treatment groups 1-9 to 1-10 are lower than those of treatment groups 1-1 to 1-8. The reason is that under the same conditions of preparing other materials and operations for the battery, the mass proportion of the functional additives in the electrolyte in treatment group 1-9 is relatively low, which is not conducive to the formation of a dense and uniform CEI film of the functional additives on the surface of the positive electrode, thereby deteriorating the normal high temperature cycle performance and average voltage of the battery; the mass proportion of the functional additives in the electrolyte in treatment group 1-10 is relatively high, and excessive film formation leads to increased impedance of the battery, and deterioration of the normal high temperature cycle performance and average voltage.

[0137] Table 2. Performance test results of Example 2

[0138]

[0139]

[0140] The test results are shown in Table 2. The treatment groups 2-1 to 2-5 were compared. The treatment group 2-1 used VC, LiFSI, MMDS and 3'-hydroxyflavanone as electrolyte additives, the treatment group 2-2 used VC, LiFSI, DTD and 3'-hydroxyflavanone as electrolyte additives, the treatment group 2-3 used VC, LiBOB, MMDS and 3'-hydroxyflavanone as electrolyte additives, the treatment group 2-4 used VC, LiBOB, PS and 3'-hydroxyflavanone as electrolyte additives, and the treatment group 2-5 used VC, LiPO 2 F 2, MMDS and 3'-hydroxyflavanone are used as electrolyte additives. It can be seen from Table 2 that in terms of the cycle capacity retention rate and average voltage at 25°C and 45°C, treatment group 2-1>treatment group 2-2, treatment group 2-3>treatment group 2-4, and treatment group 2-5. Further, by comparing treatment groups 2-1 to 2-5 with comparative treatment groups 2-1 to 2-5, it can be found that under the same conditions of other materials and operations for preparing lithium batteries, the difference between treatment group 2-1 and comparative treatment group 2-1, treatment group 2-2 and comparative treatment group 2-2, treatment group 2-3 and comparative treatment group 2-3, treatment group 2-4 and comparative treatment group 2-4, and treatment group 2-5 and comparative treatment group 2-5 is only the functional additives. However, in terms of the cycle capacity retention rate and average voltage at 25°C and 45°C, treatment group 2-1>treatment group 2-4, treatment group 2-5>treatment group 2-2 and treatment group 2-3. The reason is that compared with the functional additives shown in Formula I, the compound with a structure as shown in Formula X (structural analogues of Formula I) cannot play a synergistic role when combined with specific lithium salt additives, carbonate additives, and sulfur-containing additives, and is insufficient to further improve the battery's cycle stability and lithium ion utilization efficiency.

[0141] Similarly, the treatment groups 2-1 to 2-5 are compared with the control treatment groups 2-6 to 2-10. It can be seen from Table 2 that the lithium batteries prepared by the control treatment groups 2-6 to 2-10 are close in value in terms of cycle capacity retention and average voltage at 25°C and 45°C. The reason is that compared with the functional additives shown in Formula I, FEC (functional analogue of Formula I) cannot play a synergistic role with specific lithium salt additives, carbonate additives, and sulfur-containing additives, and is not enough to further improve the cycle stability of the battery. This shows that the functional additives shown in Formula I can play a synergistic role with specific sulfur-containing additives (MMDS), carbonate additives (VC), and lithium salt additives (LiFSI), promote the formation of CEI film, and further improve the cycle characteristics of the battery and the effective utilization rate of lithium ions.

[0142] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that: The electrolyte includes an electrolyte additive, the electrolyte additive includes a functional additive, and the structure of the functional additive is shown in Formula I; R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 are independently selected from hydrogen, C1-10 straight or branched alkyl or alkoxy, C1-10 halogenated straight or branched alkyl or alkoxy, and R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 At least one of them is a hydroxyl group.

2. The electrolyte according to claim 1, characterized in that In the formula I, at least two of R1, R2, R3, R4, and R5 are hydroxyl groups, and R7, R8, R9, R 10 At least two of them are hydroxyl groups.

3. The electrolyte according to claim 1 or 2, characterized in that The functional additive accounts for 0.3% to 1.0% by mass in the electrolyte.

4. The electrolyte according to claim 1, characterized in that The electrolyte additives also include sulfur-containing additives, carbonate additives and lithium salt additives.

5. The electrolyte according to claim 4, characterized in that The sulfur-containing additive includes at least one of methylene methanedisulfonate and vinyl sulfate; The carbonate additive includes vinylene carbonate; The lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), and lithium tetrafluoroborate.

6. The electrolyte according to claim 5, characterized in that The mass percentage of the sulfur-containing additive in the electrolyte is 0.5% to 1.0%; The mass percentage of the carbonate additive in the electrolyte is no more than 0.5%; The mass percentage of the lithium salt additive in the electrolyte is 0.3% to 1.0%; The functional additive accounts for 0.3% to 1.0% by mass in the electrolyte.

7. The electrolyte according to claim 1, characterized in that The electrolyte solution further includes an organic solvent, and the organic solvent includes a cyclic carbonate, a chain carbonate, and a chain carboxylic acid ester.

8. The electrolyte according to claim 7, characterized in that Calculated by mass ratio, the cyclic carbonate: the chain carbonate: the chain carboxylate = 1-20: 15-70: 5-20.

9. The electrolyte according to claim 1, characterized in that: The electrolyte also includes lithium salt, and the mass proportion of the lithium salt in the electrolyte is 10% to 15%.

10. A lithium battery, characterized in that: Comprising the electrolyte as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Graphite carbon fiber battery

    CN104882638A

  • Lithium metal anode and preparation and application thereof

    CN111799445A

  • Electrolyte for lithium nickel manganese oxide battery as well as preparation method and application of electrolyte

    CN117013072A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN117352671A

  • A macro-based application account management system

    KR102346480B1